Quantitation of HTLV-I and II proviral load using real-time quantitative PCR with SYBR Green chemistry - Lee, Tzong-Hae; Chafets, Daniel M.; Busch, Michael P.; Murphy, Edward L. (Journal of clinical virology, 2004)
Background: Human T-lymphotropic virus type I (HTLV-I) is linked etiologically with adult T cell leukemia/lymphoma and HTLV-I-associated myelopathy/tropical spastic paraparsis (HAM/TSP). Human T-lymphotropic virus type II (HTLV-II) is associated with HAM/TSP and, in HIV coinfected patients only, rare cases of cutaneous T cell lymphoma. Proviral load may be important in the pathogenesis of HTLV-associated disease. Materials and Methods: A real time quantitative PCR assay using SYBR Green intercalation was established. Primers targeting the tax region were standardized against MT2 and MOT cell line DNA for HTLV-I and HTLV-II, respectively. HTLV-I/II copy number was normalized to the amount of cellular DNA by quantitation of the HLA-DQ alpha gene. We measured proviral load in peripheral blood mononuclear cells (PBMCs) in a large cohort of 120 HTLV-I and 335 HTLV-II seropositive former blood donors. We also assessed the intra- and inter-assay reproducibility of the assay. Results: Proviral load for HTLV-I infected patients ranged from 3.1 × 10 0 to 1.8 × 10 5 copies/10 6 PBMCs with a mean of 1.6 × 10 4 and a median of 3.0 × 10 3. HTLV-I was undetectable in 7 of 120 cases (5.8%). Proviral load for HTLV-II infected patients ranged from 1.1 × 10 0 to 1.0 × 10 6 copies/10 6 PBMCs with a mean of 2.8 × 10 4 and a median of 5.0 × 10 2. HTLV-II was undetectable in 31 out of 335 cases (9.3%). Conclusion: The assay has excellent dynamic range from 10 6 to 10 0 copies/reaction, good intra- and inter-assay reproducibility, and a lower limit of detection of a single copy per reaction. The sensitivity and high dynamic range allow determination of a broad range of HTLV-I/II proviral load in clinical subjects. This assay will facilitate the study of the relationship between proviral load and pathogenesis.